Genomic Insights Into Five Strains of Lactobacillus plantarum With Biotechnological Potential Isolated From chicha, a Traditional Maize-Based Fermented Beverage From Northwestern Argentina - Rodrigo-Torres, Lidia; Yépez, Alba; Aznar, Rosa; Arahal, David R. (Frontiers in Microbiology, 2019)
Lactic acid bacteria (LAB) are indigenous microorganisms that have been involved in food fermentations throughout history to preserve food and also to give special characteristics to them. The traditional fermented foods that are still being elaborated in indigenous populations around the world are a potential source of LAB with important biotechnological properties and/or beneficial to health. In a previous work, LAB biodiversity associated with chicha, a traditional maize-based fermented beverage from Northwestern Argentina, was studied, both by dependent and independent methods. From that study, 392 isolates were recovered, mostly members of Lactobacillus and Leuconostoc. Biotechnological characterization of representative isolates led to the selection of five strains belonging to the species Lactobacillus plantarum for their ability to produce vitamin B2 (riboflavin) and vitamin B9 (folates), their antimicrobial properties and antibiotics susceptibility. In this work, we present the Whole Genome Sequences (WGS) of these five strains that have been deposited in the Spanish Type Culture Collection: M5MA1 (= CECT 8962), M9MM1 (= CECT 8963), M9MM4 (= CECT 8964), M9MG6 (= CECT 8965) and M9Y2 (= CECT 8966), and a detailed description of their characterization, through a genomic approach, analysing the genes responsible for these biotechnological properties, making a comparative study of the five genomes and reporting the aspects related to food safety, in accordance with the recommendations of the European Food Safety Authority (EFSA FEEDAP Panel, 2018) aiming at their use in the design of functional foods. The analysis unveiled, for the five strains, the complete set of genes for folate and riboflavin biosynthesis, the absence of pathogenic factors, the presence of CRISPR and cas genes, phage sequences, insertion elements and an aminoglycosides resistance gene, aadA, whose resistance could not be proved phenotypically in any strain. Genomic comparisons showed that strain CECT 8962 was significantly different in terms of genetic content and allowed the identification of carbohydrates metabolism and membrane transport related genes as the main components of the unique and accessory genome.